A companion to Greek art - Smith, Tyler Jo; Plantzos (Malden, MA Oxford Wiley-Blackwell, 2018)
"This well-illustrated two-volume set offers a comprehensive, authoritative account of the development of Greek art through the 1st millennium BC. While there is no shortage of introductory handbooks on Greek art, the current publication takes a fresh look at the many facets of the subject, from the basic forms, materials, and types, to colonization, iconography, and finally the reception of Greek art in post-classical periods. A Companion to Greek Art is a collaborative effort joining scholars of various nationalities and specializations. The chapter authors are foremost experts in their field, and, being drawn from the ranks of university lecturers and professors, museum curators and field archaeologists, they offer unique perspectives to the collection. As a result, this is an unbiased and inclusive representation of the state of the discipline and the current ways it is being examined by scholars all over the world. A Companion to Greek Art presents a nuanced portrait of the development of Greek art, through a narrative that is factually oriented and technically detailed, as well as thematic, contextual, and historiographical"-- Provided by publisher.
VOLUME I -- Preface -- I. Introduction -- 1. The Greeks and their Art / Tyler Jo Smith and Dimitris Plantzos -- II. Forms, Times, and Places -- 2. Chronology and Topography / Nicki Waugh -- 3. Greek Decorated Pottery I : Athenian Vase-Painting / Thomas Mannack -- 4. Greek Decorated Pottery II : Regions and Workshops / Stavros A. Paspalas -- 5. Free-standing and Relief Sculpture / Dimitris Damaskos -- 6. Architecture in City and Sanctuary / Marina Yeroulanou -- 7. Architectural Sculpture / Olga Palagia -- 8. Wall- and Panel-Painting / Dimitris Plantzos -- 9. Mosaics / Ruth Westgate -- 10. Luxury Arts / John Boardman and Claudia Wagner -- 11. Terracottas / Lucilla Burn -- 12. Coinages / François de Callataÿ -- 13. Workshops and Technology / Eleni Hasaki -- 14. Ancient Writers on Art / Kenneth Lapatin -- III. Contact and Colonies -- 15. Egypt and North Africa / Sabine Weber -- 16. Cyprus and the Near East / Tamar Hodos -- 17. Asia Minor / Veli Kose -- 18. The Black Sea / Jan Bouzek -- 19. Sicily and South Italy / Clemente Marconi -- VOLUME II -- IV. Images and Meanings -- 20. Olympian Gods at Home and Abroad / H.A. Shapiro -- 21. Politics and Society / Eleni Manakidou -- 22. Personification : Not Just a Symbolic Mode / Amy C. Smith -- 23. The Non-Greek in Greek Art / Beth Cohen -- 24. Birth, Marriage, and Death / John H. Oakley -- 25. Age and Social Identity / Jenifer Neils -- 26. Sex, Gender, and Sexuality / Timothy J. McNiven -- 27. Drinking and Dining / Kathleen M. Lynch -- 28. Competition, Festival, and Performance / Tyler Jo Smith -- 29. Figuring Religious Ritual / François Lissarrague -- 30. Agency in Greek Art / James Whitley -- V. Greek Art : Ancient to Antique -- 31. Greek Art through Roman Eyes / Michael Squire -- 32. Greek Art in Late Antiquity and Byzantium / Anthony Kaldellis -- 33. The Antique Legacy from the Middle Ages to the Enlightenment / Jill Johnson Deupi -- 34. Greek Art and the Grand Tour / Sue Blundell -- 35. Myth and the Ideal in 20th c. Exhibitions of Classical Art / Delia Tzortaki -- 36. The Cultural Property Debate / Stelios Lekakis -- 37. Greek Art at University 19th-20th c. / Stephen L. Dyson -- 38. Surveying the Scholarship / Lucie Wall Stylianopoulos -- Bibliography.
Includes bibliographical references and index.
Keywords: Art, Greek -- History